Novel Adeno-Associated Virus Vector Vaccine Restricts Replication of Simian Immunodeficiency Virus in Macaques - Johnson, Philip R. (American Society for Microbiology, 2005)
Gene transfer vectors based on recombinant adeno-associated virus (rAAV) are simple, versatile, and safe. While the conventional applications for rAAV vectors have focused on delivery of therapeutic genes, we have developed the system for delivery of vaccine antigens. In particular, we are interested in generating rAAV vectors for use as a prophylactic human immunodeficiency virus type 1 (HIV-1) vaccine. To that end, we constructed vaccine vectors that expressed genes from the simian immunodeficiency virus (SIV) for evaluation in the monkey SIV model. After a single intramuscular dose, rAAV/SIV vaccines elicited SIV-specific T cells and antibodies in macaques. Furthermore, immunized animals were able to significantly restrict replication of a live, virulent SIV challenge. These data suggest that rAAV vaccine vectors induced biologically relevant immune responses, and thus, warrant continued development as a viable HIV-1 vaccine candidate.